Application of a PCM-rich concrete overlay to control thermal induced curling stresses in concrete pavements. (20th September 2018) - Sharifi, Naser P.; Mahboub, Kamyar C.
Highlights: The weather conditions cause curling stresses in concrete pavements. Because of their cyclic nature, they cause fatigue damage in pavements. The induced cumulative fatigue Damage Index could be up to 0.22 in a concrete slab. Using a thin PCM rich concrete overlay can mitigate this deterioration mechanism. Abstract: This study aims to evaluate the application of a Phase Change Material (PCM) rich concrete overlay to reduce curling stresses in concrete pavements. Curling stresses are the results of temperature gradient in pavements, and are comparable to the stresses that are induced by traffic loads. The weather conditions, which have a cyclic nature, are the source of curling stresses, and they cause cyclic tensile and compressive stresses in pavements. This phenomenon causes fatigue damage in concrete pavements and reduces their service life. The PCMs have a high latent heat of fusion and can increase the thermal inertia of concrete. When PCM is used in a concrete overlay, it tends to moderate the temperature gradient in the slab, and thus mitigate the curling stresses. The efficiency of the proposed PCM-rich overlay was evaluated under the real climatic conditions of three different cities in the US. The findings of this research demonstrated that the cumulative fatigue Damage Index (DI) resulted from repetitive curling stresses can be up to 22% in a concrete slab with the service life of 35 years. However, using a 7.6 cm bonded concrete overlay with 25 vol% PCM can moderate the curling stresses so much that the effect of curling induced fatigue damage would be virtually negligible.